Prototipe Pencarian Berkas Kinerja Menggunakan Algoritma Knuth Morris Pratt (Studi Kasus pada Lembaga Amil Zakat) - Permatasari, Hanifah; Purwanto, Eko; Triyono, Triyono (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Operational activities at the Amil Zakat Institution (LAZ) produce various files or documents or reports or archives every year. The problem facing institutions is that the number of these reports will continue to increase over time. The management of these files has been carried out digitally using various types of information technology. The focus of information technology is not only being able to store files but also being able to find them again, so this research was conducted to optimize the performance of the search feature on file management information systems. This optimization is carried out by applying the Knuth Morris Pratt (KMP) Algorithm. The research stage is to design an algorithm for the system, build an application based on the design that has been carried out, prepare the data to be tested, and carry out testing. This research has resulted in a prototype LAZ file search. The results of testing this prototype is that the KMP Algorithm has no significant impact on search than the usual SQL Query on PHP. The test results show that the search time for files in all folders only increases by 0.095%, and the search time for files in one folder increases only by 0.007%.